The Supreme Court under Morrison R. Waite, 1874-1888 - Kens, Paul (Chief justiceships of the United States Supreme Court., 2010)
By demonstrating that there was nothing inevitable about the way constitutional doctrine has evolved, Kens provides an original and insightful interpretation that enhances our understanding of American constitutional traditions as well as the development of constitutional doctrine in the late nineteenth century.